EXAMINATION TECHNIQUES FOR TEMPOROMANDIBULAR JOINT (TMJ) CLINICAL SUBLUXATION AT THE RADIOLOGY DEPARTMENT OF RSUD BANYUMAS - Siti Nurjanah Podomi,; Amril Mukmin,; Tris Budiyono, (Journal of Innovation Research and Knowledge, 2026)
Background: Radiographic examination of the temporomandibular joint (TMJ) is an important procedure for assessing the structural condition of the joint, particularly in cases of subluxation. At the Radiology Department of RSUD (Regional General Hospital) Banyumas, this procedure is generally performed using the axiolateral projection with the Schuller method in accordance with the standard operating procedure (SOP). However, in practice, an additional AP Axial Towne projection is often used to obtain more comprehensive diagnostic results, especially for patients with a history of trauma or complex complaints. Methods: This study employed a descriptive qualitative approach using a case study method. Data were collected through direct observation, interviews with radiographers and radiologists, and documentation of patient radiographs. During the data reduction phase, collected notes and recordings were transcribed and subsequently coded using open coding techniques. Results: The addition of the AP Axial Towne projection provided enhanced visualization of the osseous structures of the TMJ, particularly the condyle and mandibular fossa. This additional projection allows radiographers to identify abnormalities such as fractures or positional changes of the condyle that may not be clearly visible using the Schuller projection alone. Conclusion: The inclusion of the AP Axial Towne projection in TMJ examinations for clinical subluxation is both effective and clinically relevant. The researchers recommend adding the Law method projection for TMJ assessment, as it uses a minimal beam angulation, reducing distortion, preventing muscle spasm, and providing more accurate anatomical representation. In addition, using a high kV technique is recommended to minimize the radiation dose received by patients.